An exploratory study of the academic leagues in southern Brazil: doing multiple activities - Diego Inácio Goergen; Ivan Carlos Ferreira Antonello; Bartira Ercília Pinheiro da Costa (Revista Brasileira de Educação Médica, 2023)
Abstract: Introduction: Academic leagues are Brazilian student-led initiatives aimed at doing multiple extracurricular activities in a medical school. The leagues exist in almost all the universities of the country. Purpose: To characterize the activity profile of the academic leagues of a medical school. Method: Quali-quantitative cross-sectional descriptive study that collected data on academic leagues such as: year of foundation, number of members, number of teachers, types of selection and admission and activities performed. Results: Of the 52 active leagues, 27 provided data. The average number of students was 21.6 ± 10.4, ranging from 07 to a maximum of 48. Most respondents (77.8%) had only one teacher. The performed activities were mainly theoretical classes, discussion of clinical cases, practical activities, production of scientific articles, publications in social networks, solidarity activities and organization of their own events. Conclusions: Academic leagues are student-led initiatives with great potential to expand medical school actions using the existing structure. With their activities mapped and guided by management, academic leagues can be great catalysts for complementary activities and can contribute greatly to the training of new doctors.